2011
DOI: 10.1177/0960327111401638
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidant and antioxidant status in infants with hyperbilirubinemia and kernicterus

Abstract: Objective: The objective of the present study was to determine oxidant and antioxidant status in infants with hyperbilirubinemia and/or kernicterus and to find whether there is a relationship between bilirubin level and oxidant/antioxidant status. Patients: The study includes 69 full-term newborns (neonates with hyperbilirubinemia needing phototherapy [Group 1, n = 36] and neonates with kernicterus [Group 2, n = 33]) and 25 age-matched healthy newborn. Results: Plasma total antioxidant capacity (TAC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Previous research shows that UCB has oxidant effects, while ω-3 PUFA demonstrates antioxidant properties [ 7 , 12 ]. To further examine this, the effects of UCB and ω-3 PUFA on SOD and CAT enzyme activity in neurons was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research shows that UCB has oxidant effects, while ω-3 PUFA demonstrates antioxidant properties [ 7 , 12 ]. To further examine this, the effects of UCB and ω-3 PUFA on SOD and CAT enzyme activity in neurons was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Bilirubin encephalopathy is a serious complication of neonatal jaundice [ 7 ]. High concentrations of UCB in the blood can easily cross the blood-brain barrier and damage neurons, resulting in neurological disability or even death [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed a significant imbalance of pro-oxidants and antioxidants in patients with CKD and diabetes [15,16,19,24,25]. It is also well known that bilirubin shows an antioxidant capacity, as in neonatal patients with increased bilirubin levels [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported lower concentration of MDA in babies with high bilirubin concentration of 20 mg/dl [41] or even 25 mg/dl [42]. Other studies declared contrary results, suggesting that this issue is still unsolved [43,44]. Researches focusing on the influence of bilirubin on total plasma antioxidant capacity (TPAC) also give inconsistent outcomes [45].…”
Section: Is Bilirubin Only a Toxic Waste Product?mentioning
confidence: 99%